Pengaruh Perubahan Penggunaan Lahan Pertambangan Terhadap Kondisi Sosial Ekonomi Masyarakat Kecamatan Bahodopi - Syaiful Azhar; Anita Indriasary; Noor Husna Khairisa; Sawaludin Sawaludin (Universitas Halu Oleo, 2023)
Mining companies provide many jobs and can increase local economic growth. The existence of a mining company in the Bahodopi sub-district has become a magnet for people to migrate, causing an increase in population and will in turn affect changes in land use and the socio-economic of community. This study aims to: (1) determine land use change as a result of mining activities; (2) know the socio-economic conditions of the community; (3) determine the effect of land use change on the socio-economic conditions of the community. The data in this study were obtained from interviews with 131 households in Bahodopi District, and were analyzed using quantitative descriptive analysis. The results of this study include: (1) changes in land use in Bahodopi District in 2014-2018 which decreased the most extensively were forests covering an area of 5.844,73 acre, while open land increased the most extensively namely 4.240,54 acre; (2) education level of society dominantly is high school (96%), from January to November 2022 there were 5.728 cases of ARI with defects at the PT IMIP health center and clinic. and most of the people earn Rp 2.100.000 - Rp 2.500.000; (3) Changes in land use that occurred in Bahodopi District resulted in an increase in population, there were many cases of ARI, and an increase in community's income.